Shape and Position of The Hands on The Bicycle Drop Bar Analysis - Elfina Rahmawati; Ali Ramadhan; Muhammad Yanuardi Irfani (Indonesian Journal of Physical Education and Sport Science)
Study Purpose. Road cycling activities are closely related to the aerodynamics and stability of the bicycle movement when used by the user. Drop bars are one of the elements of a road bike and help control speed movements while driving. Drop bars, or what is commonly known as road bike handlebars, are designed to ride at high speeds without sacrificing bike stability.